MEANINGFUL RELATIONSHIP OF ENTREPRENEURIAL COMPETENCIES AND ECONOMIC SUSTAINABILITY IN COMMUNITY-BASED RURAL TOURISM HOMESTAY PROGRAMME - Zainuddin, Nur Farrah Ain; Nor, Nor Ashikin Mohd; Ramli, Razamin (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study investigates the relationship between entrepreneurial competencies and economic sustainability in community-based rural tourism homestay programmes in the northern region of Malaysia. Familiar with the Resource-Based View (RBV) theory, the research explores how internal entrepreneurial competencies and skills serve as strategic resources that contribute to the economic sustainability of rural homestay operators. A quantitative research design was employed, involving 141 homestay entrepreneurs who responded to structured questionnaires. Data analysis was conducted using Structural Equation Modelling (SEM) to assess the measurement as well as structural models. The findings depict a significant positive connection between entrepreneurial competencies as well as economic sustainability, confirming the importance of these competencies as critical drivers for long-term financial viability in rural tourism. The results provide substantial implications for policy makers and tourism development agencies in enhancing the entrepreneurial capacity of rural communities through targeted training and support initiatives.